Association of GAK rs1564282 With Susceptibility to Parkinson’s Disease in Chinese Populations - Li, He; Zhang, Chen; Ji, Yong (Frontiers in Genetics, 2021)
The susceptibility of the GAK rs1564282 variant in Parkinson’s disease (PD) in Europeans was identified using a series of published genome-wide association studies. Recently, some studies focused on the association between rs1564282 and PD risk in Chinese populations but with inconsistent results. Thus, we conducted an updated meta-analysis with a total of 7,881 samples (4,055 PD cases and 3,826 controls) from eligible studies. After excluding significant heterogeneity, we showed that the rs1564282 variant was significantly associated with PD in Chinese populations (P = 1.00E-04, odds ratio = 1.28 and 95% confidence interval = 1.16–1.42). The sensitivity analysis showed that the association between rs1564282 and PD was not greatly influenced, and there was no significant publication bias among the included studies. Consequently, this meta-analysis indicates that the GAK rs1564282 variant is significantly associated with susceptibility to PD in Chinese populations.